2008
DOI: 10.1002/bit.22051
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange chromatography provides a robust, predictable process to ensure viral safety of biotechnology products

Abstract: The mammalian cell-lines used to produce biopharmaceutical products are known to produce endogenous retrovirus-like particles and have the potential to foster adventitious viruses as well. To ensure product safety and regulatory compliance, recovery processes must be capable of removing or inactivating any viral impurities or contaminants which may be present. Anion exchange chromatography (AEX) is a common process in the recovery of monoclonal antibody products and has been shown to be effective for viral rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
4
36
1
Order By: Relevance
“…For instance, the mechanism indicates that parameters which are important for electrostatic forces, such as salt concentration, pH, and competing ionic impurities, could have significant impacts on viral clearance. In fact, conductivity and pH have previously been shown to be important for this process (Curtis et al, 2003;Strauss et al, 2009). Conversely, our inability to observe any non-electrostatic interactions contributing to viral clearance suggests that viral clearance is less likely to be affected by residual hydrophobic impurities such as lipids or non-ionic detergents.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…For instance, the mechanism indicates that parameters which are important for electrostatic forces, such as salt concentration, pH, and competing ionic impurities, could have significant impacts on viral clearance. In fact, conductivity and pH have previously been shown to be important for this process (Curtis et al, 2003;Strauss et al, 2009). Conversely, our inability to observe any non-electrostatic interactions contributing to viral clearance suggests that viral clearance is less likely to be affected by residual hydrophobic impurities such as lipids or non-ionic detergents.…”
Section: Discussioncontrasting
confidence: 67%
“…Although most of these do not describe much characterization of the processes used, a few have demonstrated that salt concentration (or conductivity), salt composition, and pH are important factors for viral clearance (Curtis et al, 2003;Strauss et al, 2009). These correlations are consistent with those expected for electrostatic interactions, and they indicate that such interactions are necessary for a high level of viral clearance.…”
supporting
confidence: 62%
See 3 more Smart Citations